2016
DOI: 10.2463/mrms.2014-0139
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Scan Parameters to Reduce Acquisition Time for Diffusion Kurtosis Imaging at 1.5T

Abstract: Purpose: To shorten acquisition of diffusion kurtosis imaging (DKI) in 1.5-tesla magnetic resonance (MR) imaging, we investigated the effects of the number of b-values, diffusion direction, and number of signal averages (NSA) on the accuracy of DKI metrics.Methods: We obtained 2 image datasets with 30 gradient directions, 6 b-values up to 2500 s/mm 2 , and 2 signal averages from 5 healthy volunteers and generated DKI metrics, i.e., mean, axial, and radial kurtosis (MK, K ¬ , and K ¦ ) maps, from various combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Instead, we analyzed data based on two different average numbers to represent low and high signal‐to‐noise ratios, respectively. Second, the number and interval of b‐values were not numerically optimized . Note that the optimization is also dependent on signal‐to‐noise ratio which varies from study to study.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we analyzed data based on two different average numbers to represent low and high signal‐to‐noise ratios, respectively. Second, the number and interval of b‐values were not numerically optimized . Note that the optimization is also dependent on signal‐to‐noise ratio which varies from study to study.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al 19 reported that an optimized sampling scheme with three b-values (0, 1000, 2500 s/mm 2 ) achieved similar accuracy with time efficiency in stroke patients compared with the scheme with six equally spaced b-values (from 0 to 2500 s/mm 2 ). Yokosawa et al 20 reported that MK and RK estimations obtained from a dataset of 20 directions and three b-values highly agreed with those obtained from a dataset of 30 directions and six b-values. On clinical systems, Fukunaga et al 21 investigated the use of different b-values and diffusion directions combined with varied diffusion times for optimizing the DKI protocol and suggested the use of 20 directions, three b-values, and a longer diffusion time with a clinically relevant spatial resolution.…”
mentioning
confidence: 75%
“…12,13 With this protocol, DKI has a longer scan time than does DTI, and this has considerably limited the clinical usability of DKI. For reducing the scan time, previous studies 11,12,[19][20][21][22][23][24][25] have explored the effects of the number of b-values, b-value sampling schemes, and number of diffusion directions on DKI indices. Jensen and Helpern 13 suggested the use of 30 directions and three b-values (0, 1000, 2000 s/mm 2 ) as a standard DKI protocol for the brain in order to efficiently achieve accurate DKI estimation.…”
mentioning
confidence: 99%
“…Diffusion metric maps, such as mean kurtosis (MK), FA, and mean diffusivity (MD), were calculated using an in-house software program that was developed by one of the authors (S.Y.) and 6 was used in previous studies [13,14]. These maps were then non-linearly registered to the Johns Hopkins University Eve (JHU-Eve) atlas template of DiffeoMap Ver.…”
Section: Image Analysesmentioning
confidence: 99%
“…DKI source images were obtained using a single-shot spin-echo echo-planar imaging (EPI) technique with the following scanning parameters, which were optimized by a previous study [13] …”
Section: Imaging Protocolmentioning
confidence: 99%